Improving Islamic Education Learning Outcomes Through the Use of AI-Based Power Point AI-Based Media at State Senior High School 2, Bukik Barisan District - Nengsih, Sri Safri Wahyu (Jurnal Profesi Guru Indonesia, 2024)
This study aims to improve Islamic education learning in Islamic religious education learning by using power point media. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were vocational high school students. The data for this study were obtained by test and observation techniques. Tests are used to measure learning outcomes and observations are used to analyze teacher and student learning activities. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with research success indicators. The results of the study indicate that power point media can improve student learning outcomes in Islamic religious education learning. This can be seen from the increase in the percentage of student learning completion in each cycle with details of the pre-cycle 56.78%, the first cycle 63.87% and in the second cycle it increased to 70.19%. Thus, the use of power point media can be used as an alternative to improve student learning outcomes in Islamic religious education learning.